2018
DOI: 10.1364/oe.26.006962
|View full text |Cite
|
Sign up to set email alerts
|

Brillouin optical correlation domain analysis based on chaotic laser with suppressed time delay signature

Abstract: A new technology for Brillouin optical correlation domain analysis (BOCDA) based on chaotic laser is proposed, analyzed and demonstrated. The numerical simulation shows that the stimulated acoustic field has the secondary spurious peaks, which are the result of a weak amplitude autocorrelation of the chaotic signal occurring at the delay time of the external cavity, i.e., time delay signature (TDS). These secondary spurious peaks deteriorate the Brillouin gain spectrum and decrease the performance of the chaot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 28 publications
0
20
0
Order By: Relevance
“…Recently, another version of B-OCDA that shares some of the characteristics of the ASE-based approach was proposed and demonstrated by Zhang et al from Taiyuan University of Technology [34,35]. In this technique, a semiconductor laser diode is placed within an external feedback cavity, which drives the source into a chaotic regime of operation [34,35]. Noise-like waveforms of GHz-scale linewidths are obtained and used in the generation of the Brillouin pump and signal waves.…”
Section: Principle Of Operationmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, another version of B-OCDA that shares some of the characteristics of the ASE-based approach was proposed and demonstrated by Zhang et al from Taiyuan University of Technology [34,35]. In this technique, a semiconductor laser diode is placed within an external feedback cavity, which drives the source into a chaotic regime of operation [34,35]. Noise-like waveforms of GHz-scale linewidths are obtained and used in the generation of the Brillouin pump and signal waves.…”
Section: Principle Of Operationmentioning
confidence: 99%
“…Similar to ASE-based B-OCDA, high-rate external modulation of the laser light is unnecessary, and u(t) is a complex-valued random process. Care was taken to minimize secondary peaks in the auto-correlation function of the chaotic source [34]. As in phase-coded B-OCDA, pulse amplitude modulation of the pump waves was successfully introduced to suppress off-peak Brillouin interactions [35].…”
Section: Principle Of Operationmentioning
confidence: 99%
See 1 more Smart Citation
“…In Brillouin sensors, it has been demonstrated that the detected BFS value will deviate from the actual one if the temperature or strain change occurs over a length of the fiber shorter than the SR [23]. For Brillouin analysis techniques, cm-scale or even mm-scale SR has been achieved [15,24,25,26], while sub-meter SR for BOTDR is relatively hard to achieve. Therefore, researchers have proposed various methods to improve the SR of BOTDR, as listed below in Section 2.2.…”
Section: Introductionmentioning
confidence: 99%
“…HAOTIC semiconductor lasers have been used in chaos radar [1]- [5], optical reflectometry [6]- [11], Brillouin optical correlation domain analysis [12], [13], physical random number generation [14]- [17], and chaos-based secure communication [18]- [21], where advantage has been taken of the broadband nature of optical chaos. A semiconductor laser with optical feedback, optoelectronic feedback or single-beam optical injection usually generates chaos with bandwidths around several GHz which limits the range resolution of chaotic lidar, the bit rate of random sequence generation and the transmission rate of optical chaos communications.…”
Section: Introductionmentioning
confidence: 99%